Evaluation of Family-Based Interventions as a Therapeutic Tool in the Modulation of Childhood Obesity: A Systematic Review - Diego Fernández-Lázaro; Ana M. Celorrio San Miguel; Evelina Garrosa; Ana M. Fernández-Araque; Juan Mielgo-Ayuso; Enrique Roche; Soledad Arribalzaga (MDPI AG, 2024)
Childhood obesity is a major public health burden. The prevalence of weight excess for children and the adolescent population (8 to 16 years) is 34.9%. During childhood, lifestyles are acquired, which are developed in adulthood. In this context, the role of parents is crucial, since they are the model to imitate. We aimed to evaluate the current evidence on the effects of family-based interventions as a tool in the treatment of childhood obesity. We reviewed studies indexed in several databases according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Original articles published from 1 January 2014 to 30 May 2024 with a controlled trial design were considered, in which family-based interventions were carried out compared to a control group or to data before the intervention. Although 148 records were identified in the search, 6 studies met inclusion criteria. Overall, studies reported beneficial effects of family-based interventions on improving anthropometric parameters: BMI z-score, BMI, waist circumference, and body fat percentage. Regarding nutritional and physical activity guidelines, general recommendations must consider increased consumption of fruits and vegetables, reducing sugary drinks, controlled screen time, and 30-60 min of physical activity/day. Thus, family-based interventions could be an effective non-pharmacological strategy for modulating childhood obesity, allowing families to modify their lifestyles.